THE IMPACT OF RETAILER TRUST ON THE ADOPTION OF BUY NOW, PAY LATER (BNPL) SERVICES IN SAUDI ARABIA: THE MEDIATING ROLE OF SOCIAL INFLUENCE - Hatem H. Garamoun (Proceedings on Engineering Sciences)
This research sought to establish the effect of retailer trust on the usage of BNPL services in Saudi Arabia while controlling for the mediating effect of social influence. A structured questionnaire containing 24 statements was administered via the Internet, and 365 representatives from various big cities were successfully observed. This study highlights that BNPL adoption is positively im-pacted by retailers' expertise, benevolence, security, and ethical practices, and this is supported by social influence. An SEM analysis established that the social influence factor played a crucial role in how the various components of retailer trust impacted BNPL adoption, thereby enhancing posi-tivity in consumers’ attitudes toward BNPL services. The current research highlights the signifi-cance of establishing a firm foundation in resatailer trust and using social influence to encourage BNPL acceptance in emerging economies. Future studies should extend current limitations by designating longitudinal analyses, a more diverse respondent sample, and other trust aspects to deepen insights into consumers’ BNPL services.